2018
DOI: 10.26444/monz/86142
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining the acceptance of the disease in patients treated oncologically

Abstract: Cel pracy. Określenie czynników warunkujących stopień akceptacji choroby nowotworowej u pacjentów leczonych onkologicznie. Materiał i metody. Badaniem objęto 229 pacjentów Szpitala Specjalistycznego Podkarpackiego Ośrodka Onkologicznego im. ks. B. Markiewicza w Brzozowie. Dobór badanych był losowy. Zastosowano metodę sondażu diagnostycznego i technikę ankiety. Posłużono się standaryzowanym narzędziem badawczym pn. Skala Akceptacji Choroby (AIS -Acceptance of Illness Scale) w adaptacji Z. Juczyńskiego oraz auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…In the study of patients with various types of cancer, the average results of individual adjustment strategies were as follows: fighting spirit M = 22.91 (SD = 3.24), positive reevaluation M = 22.07 (SD = 2.67), anxiety M = 19.25 (SD = 3.08), helplessness–hopelessness M = 16.72 (SD = 3.38), and the choice of strategy was not influenced by the studied sociodemographic factors [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study of patients with various types of cancer, the average results of individual adjustment strategies were as follows: fighting spirit M = 22.91 (SD = 3.24), positive reevaluation M = 22.07 (SD = 2.67), anxiety M = 19.25 (SD = 3.08), helplessness–hopelessness M = 16.72 (SD = 3.38), and the choice of strategy was not influenced by the studied sociodemographic factors [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research on the acceptance of cancer was carried out by Smoleń et al on a group of 229 randomly selected respondents. It was demonstrated that the higher the degree of cancer acceptance, the lower the severity of the helplessness-hopelessness relationship [27]. Ślusarska et al assessed the level of acceptance of the disease and quality of life during treatment of patients with lymphoma using the WHO QOL-Bref questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Helplessness-hopelessness strategy indicates a passive approach to the disease, as well as a feeling of impotence and confusion. 8,9 Few scientific reports indicate the importance of assessing cancer patients' functioning and their quality of life. [10][11][12] The aim of the study was to assess the performance status, quality of life, and adaptation to the disease of elderly patients who underwent radiotherapy or chemotherapy combined with radiotherapy.…”
Section: Introductionmentioning
confidence: 99%